1986
DOI: 10.1080/00221309.1986.9710540
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana's Effects on Human Cognitive Functions, Psychomotor Functions, and Personality

Abstract: Marijuana is complex chemically and not yet fully understood, but it is not a narcotic. Like alcohol, marijuana acts as both stimulant and depressant, but it lingers in body organs longer than alcohol. Smoking marijuana can injure mucosal tissue and may have more carcinogenic potential than tobacco. Research has indicated that marijuana intoxication definitely hinders attention, long-term memory storage, and psychomotor skills involved in driving a car or flying a plane. Expectations and past experience with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 197 publications
0
16
0
Order By: Relevance
“…Seventy age-matched participants (N = 35 men; N = 35 women) were randomly assigned to smoke either an active or placebo marijuana cigarette in a double-blind, between-subjects design after which they completed a standardized neuropsychological test battery. Active marijuana impaired selective and divided attention and time estimation (Murray 1986; O'Leary, et al 2003; Wilson, Ellinwood, Mathew, & Johnson 1994). …”
Section: Discussionmentioning
confidence: 99%
“…Seventy age-matched participants (N = 35 men; N = 35 women) were randomly assigned to smoke either an active or placebo marijuana cigarette in a double-blind, between-subjects design after which they completed a standardized neuropsychological test battery. Active marijuana impaired selective and divided attention and time estimation (Murray 1986; O'Leary, et al 2003; Wilson, Ellinwood, Mathew, & Johnson 1994). …”
Section: Discussionmentioning
confidence: 99%
“…Administration of cannabinoid (CB) agonists results in some well‐characterized behavioural changes such as hypolocomotion, hypothermia, catalepsy and analgesia in animals (Abood & Martin, 1992). In addition, cannabinoids are well‐know for their ability to disrupt information processing, attention and memory in animal and human subjects (Murray, 1986; Heyser et al ., 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In a study with oral THC, participants who expected to receive a cannabinoid reported greater pleasurable effects and desire to consume more than those without this expectancy (Kirk, Doty, & de Wit, 1998). Similarly, subjective effects experienced by marijuana smokers were more influenced by contextual factors such as set and setting than by THC content (Murray, 1986). …”
mentioning
confidence: 99%